Recommendation System Selection of Boarding House Using Website Based Profile Matching Method - Martoni, Robi; Rahmadika, Sandi; Kurniadi, Denny; Delianti, Vera Irma (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
The increasing demand for boarding houses in Padang City, especially from students, raises challenges in choosing a place to live that suits their needs. This research aims to develop a web-based boarding house selection recommendation system using the Profile Matching method. This method matches the user’s ideal profile with the actual profile of the boarding house based on criteria such as price, distance, room size, and facilities. The system is designed and developed with a focus on applying the Profile Matching method, which calculates the difference (gap) between ideal and actual profiles to produce the best recommendation. System testing was conducted through Whitebox Testing and Rating Validation Test to assess the accuracy of the system. The results show that the system is able to provide boarding house recommendations effectively with an accuracy of 100%. This system is expected to help students in making more efficient and directed decisions.